Chinese Circulations Capital, Commodities, and Networks in Southeast Asia - Tagliacozzo, Eric; Chang, Wen-Chin (Duke University Press, 2011)
Chinese merchants have traded with Southeast Asia for centuries, sojourning and sometimes settling, during their voyages. These ventures have taken place by land and by sea, over mountains and across deserts, linking China with vast stretches of Southeast Asia in a broad, mercantile embrace. Chinese Circulations provides an unprecedented overview of this trade, its scope, diversity, and complexity. This collection of twenty groundbreaking essays foregrounds the commodities that have linked China and Southeast Asia over the centuries, including fish, jade, metal, textiles, cotton, rice, opium, timber, books, and edible birds' nests. Human labor, the Bible, and the coins used in regional trade are among the more unexpected commodities considered. In addition to focusing on a certain time period or geographic area, each of the essays explores a particular commodity or class of commodities, following its trajectory from production, through exchange and distribution, to consumption.